The agonistic mosaic in the Villa of Lucius Verus and the Capitolia of Rome. (27th October 2015) - Dunbabin, Katherine M. D.
Abstract : The 3rd-c. interventions in the Villa of Lucius Verus on the Via Cassia included the laying of a black-and-white mosaic in the irregular space 32 in Sector D, which forms a passage or vestibule between exedra 24/25 to the north and the small baths (41–48) to the south (fig. 1). The mosaic shows a series of figures and small groups; most are athletes of various sorts, but they also include musicians, comic and tragic actors, and a prize-table with crowns or wreaths and busts of the three Capitoline deities, as well as other figures whose identification is sometimes not immediately obvious (fig. 2). The combination of athletic, musical and theatrical events is the characteristic mark of a Greek agon ; the mosaic therefore takes its place among a small group of monuments that portray such agones . As a detailed description of the mosaic was presented by E. Caserta in NSc 22 (2010–11), the object of the present article is to place the mosaic in the context of related monuments, discuss the more problematic figures, and consider iconographic parallels which not only help to clarify some of the problems but can also indicate the artistic context within which its designer was working. Finally, it will consider the overall interpretation of the mosaic and its relationship to the agonistic culture of Rome in the 3rd c. A.D.